Reticulate pigmentation associated with scarring alopecia in an elderly woman: An unusual manifestation of lichen planus pigmentosus - Vinod Kumar Sharma; Neetu Bhari; Sweta Subhadarshani; Neha Taneja; Rakesh Kumar Deepak (Wolters Kluwer Medknow Publications, 2016)
A 70-year-old woman presented with generalized reticulate pigmentation, scarring alopecia, and few discrete, violaceous plaques over the trunk and forearm. Dermoscopic evaluation of the reticulate plaque showed reticulate hyperpigmentation with multiple telangiectasias, and skin biopsy showed lichenoid interface dermatitis with marked pigment incontinence. Thus, a final diagnosis of poikiloderma due to lichen planus pigmentosus was considered.